PEMERINGKATAN PENILAIAN KINERJA KARYAWAN MELALUI METODE AHP DAN VIKOR - Yusnaeni, Wina; Marlina, Marlina (Jurnal Pilar Nusa Mandiri, 2019)
In the company can not be separated from human resources, which is an important part of the company. The success of a company depends on the resources that are in it. Therefore, human resources have a very vital role. One of the most important factors in a company, human resources must be considered for their welfare and appreciation. For example, giving appreciation for employee performance. From evaluating employee performance, exact calculations are required, one of which uses AHP and Vikor methods. The result of this research showed usage method of vikor who assists in assessment has raised the of employee performance based on the criteria of which there are, Where criteria have been in appointed by the company and provision of weight of criteria with the methods ahp. From the results of the count it over with ahp drugs got when the the value of weighted criteria in accordance with the provisions fees for civil servant employees ahp with a value of The CR ≤ 0.1. This is done to explain the consistency of the weight of the criteria which had been assessed by the judges. Next, with Vikor method, obtained with the smallest value in the calculation of V = 0.5. from the results of the performed calculations to see stability calculation results with alternative methods of vikor 1 way obtained Value Q (2)-Q (1) ≥ DQ,. and obtained also for method 2 using the value V = 0.4 and value V = 0.6 and gained equality results ranked one and two. The result of the method of vikor expected can help decision-makers in determining the ranking of employees based on the best performance of employees.